Strengthening food safety policy: a case study of the food safety policy landscape in Sri Lanka - Anowarul I. Bokshi; Samali C. Perera; Joy A. Becker; Mark Bradbury; Yu-Wen Lai; Ilmi G.N. Hewajulige; Anne-Marie Thow; Daniel K.Y. Tan (Applied Food Research, 2025)
Food safety is critical to nutrition and wellbeing, and is an important contributor to the achievement of sustainable development. There is public concern in Sri Lanka over food hazards originating from primary production, and unsafe use of chemicals in commonly consumed food items. Food contamination poses particular health threats to urban communities due to their dependence on the informal supply chain. The high risks for foodborne-disease outbreaks in Sri Lanka are also a major constraint for the export market. This paper presents the findings from a documentary policy analysis and literature review, with the aim to understand the current situation of food contaminations across the food production and supply chains of Sri Lanka, and the current policy context, and provide recommendations to address food safety issues at the national level. The Food Act No 26 (1980) is the main control measures in ensuring food safety that relies on product assessment, which is complemented by policy measures across multiple sectors. However, we observed limited policy attention to preventative food safety management, and food safety measures addressing agricultural production and food supply chain management. Based on the literature, we identified concerning exposure of food products to pesticides, heavy metals, mycotoxin, microbial contamination, and food adulteration. Sri Lanka needs to build capacity with infrastructure and human resource development to facilitate food safety management and supervision. For sustainable food safety regulation, the agriculture, health, and trade sectors should formulate consistent policies for regular monitoring, to conduct research on food safety risks and quality assurance, and support relevant departments in implementing control practices.